Dynamics of a Chemoattractant Receptor in Living Neutrophils during Chemotaxis - Servant, Guy (The American Society for Cell Biology, 1999)
Persistent directional movement of neutrophils in shallow chemotactic gradients raises the possibility that cells can increase their sensitivity to the chemotactic signal at the front, relative to the back. Redistribution of chemoattractant receptors to the anterior pole of a polarized neutrophil could impose asymmetric sensitivity by increasing the relative strength of detected signals at the cell’s leading edge. Previous experiments have produced contradictory observations with respect to receptor location in moving neutrophils. To visualize a chemoattractant receptor directly during chemotaxis, we expressed a green fluorescent protein (GFP)-tagged receptor for a complement component, C5a, in a leukemia cell line, PLB-985. Differentiated PLB-985 cells, like neutrophils, adhere, spread, and polarize in response to a uniform concentration of chemoattractant, and orient and crawl toward a micropipette containing chemoattractant. Recorded in living cells, fluorescence of the tagged receptor, C5aR–GFP, shows no apparent increase anywhere on the plasma membrane of polarized and moving cells, even at the leading edge. During chemotaxis, however, some cells do exhibit increased amounts of highly folded plasma membrane at the leading edge, as detected by a fluorescent probe for membrane lipids; this is accompanied by an apparent increase of C5aR–GFP fluorescence, which is directly proportional to the accumulation of plasma membrane. Thus neutrophils do not actively concentrate chemoattractant receptors at the leading edge during chemotaxis, although asymmetrical distribution of membrane may enrich receptor number, relative to adjacent cytoplasmic volume, at the anterior pole of some polarized cells. This enrichment could help to maintain persistent migration in a shallow gradient of chemoattractant.